2021
DOI: 10.1177/10820132211019143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and soluble solid onBacillus subtilisandBacillus licheniformisspore inactivation and quality degradation of pineapple juice

Abstract: Bacillus subtilis and Bacillus licheniformis spores can survive processing temperatures used in the thermal processes of high-acid foods. Therefore, this study investigated the thermal inactivation of B. subtilis and B. licheniformis spores in pineapple juice at different temperatures (85–100°C) and soluble solids (SS, 11–30°Brix). The quality of juices and microbial loads after the thermal treatments during storage at 4 °C for 35 days was then checked. A linear decrease in D-value was observed with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Evelyn et al. (2021) used PEF (11.3 pulses at 65 kV/cm) for the inactivation of Eupenicillium Javanicum ascospores in the pineapple juice with varying total soluble solids (TSS of 10–30 °Brix). They obtained 4.0, 3.1, and 1.3 log cycle reductions in the ascospore population with TSS levels of 10, 20, and 30 °Brix, respectively.…”
Section: Nonthermal Processing Of Pineapple Juicementioning
confidence: 99%
See 1 more Smart Citation
“…Evelyn et al. (2021) used PEF (11.3 pulses at 65 kV/cm) for the inactivation of Eupenicillium Javanicum ascospores in the pineapple juice with varying total soluble solids (TSS of 10–30 °Brix). They obtained 4.0, 3.1, and 1.3 log cycle reductions in the ascospore population with TSS levels of 10, 20, and 30 °Brix, respectively.…”
Section: Nonthermal Processing Of Pineapple Juicementioning
confidence: 99%
“…In the last decade, pasteurization of pineapple juice was explored using various nonthermal treatments. These include PEF (Abu et al, 2020;Dastgheib et al, 2014;Evelyn et al, 2021;Indriani et al, 2019), ultrasound (US) treatment (Bevilacqua et al, 2014;Paniagua-Martínez et al, 2018;Yeoh & Ali, 2017), pulsed light (PL) (Preetha et al, 2016(Preetha et al, , 2021Vollmer, Chakraborty, et al, 2020), high-pressure processing (HPP) (Wu et al, 2021), and pressure change technology (PCT) (Vollmer et al, 2021;Vollmer, Santarelli, et al, 2020). To add more, some of the researchers also explored kinetic modeling of degradation of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The extrapolated D 121 values were 0.57, 0.76, 0.71, and 1.45 min, respectively. Evelyn et al (2021) determined that the D-values for B. subtilis in 11 °Brix pineapple juice were 2.1 ± 1.7 min at 100 °C, 6.8 ± 0.9 min at 95 °C, and 13.2 ± 0.5 min at 90 °C (p < 0.05). Moreover, Rodriguez et al (1993) reported the D-values for B. subtilis 075-T-0 in tomato juice were 5.7 min at 100 °C and 15.8 min at 95 °C.…”
Section: Spore Heat Resistancementioning
confidence: 97%
“…Juice of many fruits are probably the natural habitat of Bacillus spp. as reported by Alwakeel and Al-Humaidi (2008), Aneja et al (2014), andEvelyn et al (2022). This study was carried out to apply a juice-based medium for the proliferation of Bacillus strain(s) that antagonize Phytophthora capsici, Rhizoctonia solani, and Sclerotium rolfsii.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 94%